Spatio-temporal variation and prediction of ecological quality based on remote sensing ecological index – a case study of Zhanjiang City, China - Wang, Jing; Wang, Jia; Xu, Jiangqi (Frontiers in Ecology and Evolution, 2023)
A significant portion of Zhanjiang City’s ecological land areas have been reduced as a result of the city’s growing urbanization, which has caused the city’s ecological environment quality to decline. In order to monitor the quality of the ecological environment, the remote sensing ecological index (RSEI) is frequently utilized. In this study, the Landsat series satellite images from 2000, 2005, 2009, 2015, and 2020 were used. The Normalized Differential Vegetation Index (NDVI), Wetness (WET), Normalized Differential Build-up and bare Soil Index (NDBSI), and Land Surface Temperature (LST) were the four indicators utilized in the RSEI to quantitatively evaluate the changes in ecological environment quality in Zhanjiang City. The results are as follows. (1) The mean RSEI values for the years 2000, 2005, 2009, 2015, and 2020 are, respectively, 0.579, 0.597, 0.597, 0.607, and 0.601. In addition, the overall ecological environment of Zhanjiang is very good. In terms of spatial differences, the ecological environment quality in the central and southeastern parts of Zhanjiang is significantly higher than that in other areas, while the ecological environment quality in its coastal town areas is much worse. The lower RSEI index of developed land in coastal areas proves that the RSEI index can reflect the deterioration of the urban environment in coastal areas from 2000 to 2020. Therefore, the RSEI can be used to evaluate the ecological environment quality of Zhanjiang City. (2) The ecological environment changes in the study area are “substantially better,” “better,” “no change,” “worse,” and “much worse,” respectively, according to the difference in RSEI processed between 2000 and 2020. These changes were 38.38, 6,047, 13.93, 6.65, and 34.58%. The percentage of ecological environmental quality in Zhanjiang City that has become better is higher than that has become worse. This indicates that the quality of ecological environment in Zhanjiang City has improved between 2000 and 2020. (3) The regression produced the following equation for the association, which was significant at the 0.053 level: 100*Rsei = 154.69–1.18*IS(R = 0.66). The remote sensing ecological index for Zhanjiang in 2035 is 0.488 when the city’s planned population and area are added together.